USE OF FORECASTING AND MODELING METHODS FOR OPTIMIZATION OF HOTEL, RESTAURANT AND TOURIST BUSINESS DEVELOPMENT MANAGEMENT - Kolontaievskyi, O.; Shapovalenko, D. (Municipal economy of cities. Series: «Economy science», 2022)
The purpose of the article is to determine directions for the use of forecasting and modeling methods to optimize management of the development of the hotel and restaurant business. Types and methods of forecasting are listed. Classifications of forecasting methods were studied and their main groups were listed. The advantages and disadvantages of forecasting and modeling methods that are most commonly used in practice are analyzed. It was determined that the advantage of expert forecasting methods is relative simplicity for any situations, including in conditions of incomplete information. It is noted that simple methods of extrapolation can be used at the initial stage of forecasting to determine trends in changes in indicators. Complex methods of extrapolation can be used in the development of short-term forecasts. Smoothing methods are auxiliary in forecasting, which are used in combination with the main ones. It is noted that modeling methods can be used to determine the influence of various factors on the development of economic processes in the hotel and restaurant business. The advantages and disadvantages of the method of the annual average of the index are analyzed. The content of the forecasting methods themselves significantly depend on the terms of the forecasts. It was determined that when forecasting the development of hotel and restaurant business enterprises, it is most appropriate to use combined methods that combine economic-mathematical modeling and development scenarios inherent in intuitive methods. Recommendations for the use of cluster analysis of hotel and restaurant business enterprises are presented and the results of this analysis are determined. The stages of cluster analysis of a group of hotels and its results are described. It is noted that the possibilities of practical use of this or that forecasting method are determined by the purpose of the forecasting results, the features of the object, and the availability of the necessary information.